ҚАРАҚАЛПАҚ ӘДЕБИЯТЫ ҲӘМ ШЫҒЫС ПОЭЗИЯСЫНЫҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИГИ - Давлетов, Б. (SCIENCE and SOCIETY, 2018)
The article deals with the genre of byte in the creation of the poets of Karakalpak literature of the XIX –th century Ajiniyaz and Kazi Mavlik on the basis of the literary and other materials.
Keywords: history of literature; creation of the poets Ajiniyaz and Kazi Mavlik; humanistis ideas